Analysis of soil profiles in dwarf-shrub vegetation in South Greenland. - Hansen, Kjeld (Meddelelser om Grønland, 1969)
In 1965 analyses were made of vegetation and soil profiles in South Greenland, al about 62° lat. N, in 13 localities with different types of dwarf-shrub vegetation, situated at 3 stations at different distances from the outer coast. Results are given of analyses of each layer in each of the 13 soil profiles, comprising the depth of the layer, its colour, content of organic matter, particle size, pH, conductivity, contents of exchangeable K, Na, Ca, Mg, and Mn, content of P (extracted by means of 0.2 N H2SO4), and contents of Fe, Cu, Zn, and Pb (extracted by means of EDTA). A summary is given of the average values of measurements of edaphic conditions in each layer of the profiles at each station. The vertical variation of these values has been found to depend on the soil material, as well as on the distance of the station from the outer coast. Profiles on gneissic material show, at an increasing depth, a decrease in the contents of organic matter, of conductivity, and of the contents of K, Na, Ca, Mg, Mn, Fe, Cu, and Zn-an increase in pH and in the content of P, but mostly an almost unchanged content of Pb. A profile on diabasic material for all edaphic factors shows approximately the same value in the layers. The profiles at the off-shore station, with a relatively low amount of precipitation, are those most faintly differentiated, while the profiles at the near-shore station, with a higher amount of precipitation, show a pronounced podsolization. Furthermore, a certain connection has been found between type of profile and vegetation. Some species of dwarf-shrubs are mainly connected with diabasic, or with off-shore profiles, while other species have the highest frequencies on podsolized, gneissic profiles near the outer coast.